Interviews - Matt, Gerald; Aparicio, Eduardo; Barney, Matthew; Beecroft, Vanessa; Cai Guo-Qiang; Cantor, Ellen; Jermolaewa, Anna; Kim, Soo-Ja; Krystufek, Elke; Matt, Gerald; McQueen, Steve; Medoune Seye, Bouna; et al. (Wien : Kunsthalle Wien, 2003)
Aparicio, Eduardo ; Barney, Matthew ; Beecroft, Vanessa ; Cai Guo-Qiang ; Cantor, Ellen ; Jermolaewa, Anna ; Kim, Soo-Ja ; Krystufek, Elke ; McQueen, Steve ; Medoune Seye, Bouna ; Moffatt, Tracey ; Neshat, Shirin ; Sierra, Santiago ; Tomic, Milica
boek